Analysis of Marketing Strategies with Marketing Mix at the Pratama Clinic of the Malang Police Station Using the SOAR Method - Sitompul, Adriel; Waluyo, Minto (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Malang District Police Principal Clinic is a first level health facility. Referring to the website of the Ministry of Health (Kemenkes) regarding Health Service Units (UPK), Based on existing data, there is a decrease in the number of visitors every year, starting from 2018 to 2022. The purpose of this study is to see how the implementation of marketing strategies using marketing mix at the Pratama Clinic of the Malang Police with the SOAR method. This research uses the soar analysis method which serves to analyze how the implementation of existing marketing strategies. The results of this study are that the implementation strategy implemented by this clinic has not been effective, based on the results of data processing through the IFE, EFE, and IE matrices from the questionnaires distributed, the results show that the marketing strategy that has been carried out at the Pratama clinic of the Malang police with the IFE score and EFE score in the IE matrix is in quadrant V (Medium-Medium) with the condition of hold and maintain (Market penetration and system development). From both IFE and EFE scores, the difference is quite small, meaning that both have a balanced point that is not too strong and not too weak. This proves that in the eyes of visitors to the Pratama clinic of the Malang police station there are still several things that need to be improved.